IMPROVEMENT OF THE TECHNOLOGY FOR PRODUCING ECO-FRIENDLY BIOPLASTIC MATERIAL USING EGGSHELL WASTE AS A NATURAL MINERAL FILLER - S.N.Obloberdiyev,; G.Sh.Korabekova,; F.Sh.G‘ulomova,; Sh.E.Ulashova,; M.J.Bekmurodova,; Z.A.Madusmonova, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This study focuses on improving the technology for producing eco-friendly bioplastic material using eggshell waste as a natural mineral filler. Eggshell powder was added to a biodegradable polymer matrix to enhance the strength, density, and structural stability of the material. The obtained bioplastic showed improved physical and technological properties, indicating that eggshell waste can be effectively used as a low-cost, available, and environmentally safe raw material for biodegradable material production.